P‐91: Improving Light Extraction from QD‐LED Pixels. Issue 1 (25th September 2020) - Montgomery, David J.; Boardman, Edward A.; Smeeton, Tim M.; Gass, Paul A.
Abstract : We introduce a new dual‐cavity structure for QD‐LED pixels using a second metal layer above the cathode and a silicon dioxide layer between them. Hybrid optical simulation of the bank pixel structures for red, green and blue sub‐pixels show how this improves extraction efficiency and minimizes colour shift.